SPEECH ACT OF CRITICIZING, PERSUADING THE AUDIENTS BELIEVES ON â€œWAR MACHINEâ€ FILM: A PRAGMATIC MUTIMODAL PERSPECTIVE - Syaifuddin S, M.; Djatmika, .; Kristina, Diah; Wiratno, Tri (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2018)
This aims to reveal the ways of criticizing American government and wheedling the audients believe trough each speech act in movie. Pragmatic multimodal perspective is used to uncover both speech act and the cinematic aspect in order to know how the movie producer criticize and persuade audients to believe. This research is presented Qualitatively and the data taken from David MichÃ´d (2016) work â€œWar Machinesâ€. It was found that the movie has three ways in criticizing the government and persuading the audien to believe. They are; 1. To contradict between speech and multimodality of cinematic to create an offensive criticism structure. 2. Use of mutually supportive between speech acts of and multimodality to create a common criticism structure (mutual affirmation of speech acts and multimodality). 3. The use of personification of institutions to direct criticism of policy holders.Â Â